Tuberculous Liver Abscess with Right Sided Pleural Effusion - Yadav, Prashant; Punera, Dinesh Chandra; Nautiyal, Ramgopal; Kumar, Anand (Indian Journal of Case Reports, 2020)
Tuberculosis is a rare cause of liver abscess even in countries where the tuberculosis is prevalent, liver may be involved as a part of miliary tuberculosis or as local tuberculosis. We present a case of tuberculous liver abscess in patient with smearpositive pulmonary tuberculosis and right pleural effusion. A positive BACTEC culture and Polymerase chain reaction (PCR) for Acid Fast Bacilli (AFB) in the pus aspirated from abscess confirmed the diagnosis of tuberculous liver abscess.